Tau PET With 18F-THK-5351 Taiwan Patients With Familial Alzheimer's Disease With the APP p.D678H Mutation - Huang, Chin-Chang; Hsiao, Ing-Tsung; Huang, Chu-Yun; Weng, Yi-Ching; Huang, Kuo-Lun; Liu, Chi-Hung; Chang, Ting-Yu; Wu, Hsiu-Chuan; Yen, Tzu-Chen; Lin, Kun-Ju (Frontiers in Neurology, 2019)
Background Brain 18F-AV-45 amyloid positron emission tomography (PET) in Taiwanese patients with familial Alzheimer’s disease with the amyloid precursor protein (APP) p.D678H mutation tends to involve occipital and cerebellar cortical areas. However, tau pathology in patients with this specific Taiwan mutation remains unknown. In this study, we aimed to study the Tau PET images in these patients. Methods Clinical features, brain magnetic resonance imaging/computed tomography (MRI/CT), and brain 18F-THK-5351 PET were recorded in five patients with the APP p.D678H mutation and correlated with brain 18F-AV-45 PET images. We also compared the tau deposition patterns among five patients with familial mild cognitive impairment (fMCI), six patients with sporadic amnestic mild cognitive impairment (sMCI), nine patients with mild to moderate dementia due to Alzheimer’s disease (AD), and 12 healthy controls (HCs). All of the subjects also received brain 18F-AV-45 PET. Results The nine patients with sAD and six patients with sMCI had a positive brain AV-45 PET scans, while the 12 HCs had negative brain AV-45 PET scans. All five patients with fMCI received a tau PET scan with the age at onset ranging from 46 to 53 years, in whom increased standard uptake value ratio (SUVR) of 18F-THK-5351 was noted in all seven brain cortical areas compared with the HCs. In addition, the SUVRs of 18F-THK-5351 were increased in the frontal, medial parietal, lateral parietal, lateral temporal, and occipital areas (P<0.001) in the patients with sAD compared with the HCs. The patients with fMCI had a significant higher SUVR of 18F-THK-5351 in the cerebellar cortex compared to the patients with sMCI. The correlations between regional SUVR and Mini-Mental State Examination score and between regional SUVR and clinical dementia rating (sum box) scores within volumes of interest of Braak stage were statistically significant. Conclusion Tau deposition was increased in the patients with fMCI compared to the HCs. Increased regional SUVR in the cerebellar cortical area was a characteristic finding in the patients with fMCI. As compared between amyloid and tau PET, the amyloid deposition is diffuse, but tau deposition is limited to the temporal lobe in the patients with fMCI.